2019
DOI: 10.1371/journal.pone.0217438
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq profiles of chicken type II pneumocyte in response to Escherichia coli infection

Abstract: Avian pathogenic Escherichia coli (APEC) causes great economic loss to the poultry industry worldwide. Chicken type II pneumocytes (CP II cells) secrete surfactants and modulate lung immunity to decrease the infection of the invading pathogen. Nevertheless, the pathogenesis of CP II cells to APEC infection remains poorly understood. Therefore, we conducted global gene expression profiling of CP II cells after APEC-O78 infection to explore the host-pathogen interaction. The differentially expressed genes of CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To explore the host–pathogen interaction, a response in global gene expression profiling of chicken type II pneumocytes (CP II cells), responsible for secreting surfactants and modulating lung immunity, to avian pathogenic Escherichia coli (APEC-O78) infection was determined. In fact, CP II cells were shown to respond to APEC infection with marked changes in the expression of 1390 genes (from 18,996 genes identified) with 803 downregulated mRNAs and 587 upregulated mRNAs [ 266 ]. The major enriched pathways were identified to be related to the NF-κB signaling pathway, apoptosis pathway, tight junction, and cytokine–cytokine receptor interaction.…”
Section: Effect Of Various Stress Factors On Nf-κb Expression Andmentioning
confidence: 99%
“…To explore the host–pathogen interaction, a response in global gene expression profiling of chicken type II pneumocytes (CP II cells), responsible for secreting surfactants and modulating lung immunity, to avian pathogenic Escherichia coli (APEC-O78) infection was determined. In fact, CP II cells were shown to respond to APEC infection with marked changes in the expression of 1390 genes (from 18,996 genes identified) with 803 downregulated mRNAs and 587 upregulated mRNAs [ 266 ]. The major enriched pathways were identified to be related to the NF-κB signaling pathway, apoptosis pathway, tight junction, and cytokine–cytokine receptor interaction.…”
Section: Effect Of Various Stress Factors On Nf-κb Expression Andmentioning
confidence: 99%
“…It was shown in vitro that embryonic primary type II pneumocytes belonging to the squamous epithelial cells possess important roles as an entry barrier for pathogens including APEC and as modulators of the local immune response. The transcriptome of primary chicken type II pneumocytes after stimulation with a high dose of APEC O78 (a multiplicity of infection (MOI) of 100) suggested that the major enriched pathways were related to the NF-κB signalling pathway, apoptosis, tight junctions, and cytokine-cytokine receptor interactions, with IL1B, IL6 and IL18 upregulated (Peng et al, 2019b). Several plant-derived substances can modulate the type II pneumocyte immune response to APEC, for example rutin, astragaloside IV, α-cyperone, baicalin, and schizandrin may reduce cell damage of type II cells after APEC O78 exposure (Zhang et al, 2014;Zhang et al, 2016;Peng et al, 2018b;Peng et al, 2019a;Peng et al, 2019c;Yuan et al, 2020a;Yuan et al, 2020b).…”
Section: The Epithelial Barriermentioning
confidence: 99%
“…High-throughput sequencing techniques have become powerful and effective tools for gaining a deeper understanding of the basic molecular mechanisms of complicated systems ( Wang et al, 2009 ; Ozsolak and Milos, 2011 ). RNA sequencing, a high-throughput technique, has been generally used in livestock to find the expression patterns of functional genes ( Cui et al, 2017 ; Ni et al, 2019 ; Peng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%